1998
DOI: 10.1046/j.1365-201x.1998.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and neuroendocrine peptides influence DNA synthesis in rat and human small intestinal cells in vitro

Abstract: Animal studies suggest a mediator role for neuroendocrine peptides and amines in regulating cell proliferation in the gastrointestinal epithelium. Our aim was to examine the effect of serotonin and selected gastrointestinal peptides on DNA synthesis in a rat and human small intestinal cell line in vitro. IEC-6 and FHs-74 cells were incubated with epidermal growth factor (EGF), insulin-like growth factor II, glucagon, substance P, neurokinin A, calcitonin gene-related peptide (GRP, CCGRP), neurotensin and serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…IEC-6 cells are nontransformed small intestinal epithelial cells that retain receptors to growth factors [42]and possess cell kinetics characteristics that resemble those of human antral epithelial cells [43, 44]. It is noteworthy that the vast majority of the cells used in our study were viable, as shown by trypan blue exclusion and by the flow cytometric analysis with propidium iodide/annexin-V staining (fig.…”
Section: Discussionmentioning
confidence: 87%
“…IEC-6 cells are nontransformed small intestinal epithelial cells that retain receptors to growth factors [42]and possess cell kinetics characteristics that resemble those of human antral epithelial cells [43, 44]. It is noteworthy that the vast majority of the cells used in our study were viable, as shown by trypan blue exclusion and by the flow cytometric analysis with propidium iodide/annexin-V staining (fig.…”
Section: Discussionmentioning
confidence: 87%
“…Adding to that, experiments using co-cultures indicate that human submucosal neurons might control the intestinal epithelium, since disorganization and proliferation occured in the absence of neuronal activation (Toumi et al 2003). Serotonin, in contrast to other factors, inhibits intestinal cell proliferation in vitro (Zachrisson & Uribe 1998). Our results indicate that serotonin cell population is diminished after myenteric ablation, and this response is concomitant with the enlargement of submucous VIP neurons (Hernandes et al, 2004).…”
Section: Discussionmentioning
confidence: 68%
“…Enteroendocrine cells are characterized by the presence of numerous granules that contain chemical mediators, which are active on the secretory, absorptive and motor functions (Ormsbee & Fondacaro 1985). Although the mediators have been identified (Sjo´lund et al 1983), the main product of these cells is serotonin (Inokuchi et al 1983, Hocker & Wiedenmann 1998, which was shown to inhibit the proliferation of intestinal cells in vitro (Zachrisson & Uribe 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Intraluminal bacteria modulate the endocrine cell system and the synthesis or release of neuroendocrine peptides (8) with known mitogenic actions on epithelial cells (9,10). In addition, bacteria and bacterial-derived antigens in uence immune and other intestinal mucosa cells and modulate the production of cytokines (10) which are potent stimulators of DNA synthesis in lymphocytes (11,12) and other cell types, including intestinal epithelial cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bacteria and bacterial-derived antigens in uence immune and other intestinal mucosa cells and modulate the production of cytokines (10) which are potent stimulators of DNA synthesis in lymphocytes (11,12) and other cell types, including intestinal epithelial cells (4). Moreover, bacteria possess mitogens that can directly stimulate DNA synthesis of epithelial cell lines in ×itro (6).…”
Section: Introductionmentioning
confidence: 99%